AraPerox: a database of putative Arabidopsis proteins from plant peroxisomes - Reumann, Sigrun; Ma, Changle; Lemke, Steffen; Babujee, Lavanya (Plant physiology, 2004)
To identify unknown proteins from plant peroxisomes, the Arabidopsis genome was screened for proteins with putative major or minor peroxisome targeting signals type 1 or 2 (PTS1 or PTS2), as defined previously (Reumann S [2004] Plant Physiol 135: 783-800). About 220 and 60 proteins were identified that carry a putative PTS1 or PTS2, respectively. To further support postulated targeting to peroxisomes, several prediction programs were applied and the putative targeting domains analyzed for properties conserved in peroxisomal proteins and for PTS conservation in homologous plant expressed sequence tags. The majority of proteins with a major PTS and medium to high overall probability of peroxisomal targeting represent novel nonhypothetical proteins and include several enzymes involved in β-oxidation of unsaturated fatty acids and branched amino acids, and 2-hydroxy acid oxidases with a predicted function in fatty acid α-oxidation, as well as NADP-dependent dehydrogenases and reductases. In addition, large protein families with many putative peroxisomal isoforms were recognized, including acyl-activating enzymes, GDSL lipases, and small thioesterases. Several proteins are homologous to prokaryotic enzymes of a novel aerobic hybrid degradation pathway for aromatic compounds and proposed to be involved in peroxisomal biosynthesis of plant hormones like jasmonic acid, auxin, and salicylic acid. Putative regulatory proteins of plant peroxisomes include protein kinases, small heat shock proteins, and proteases. The information on subcellular targeting prediction, homology, and in silico expression analysis for these Arabidopsis proteins has been compiled in the public database AraPerox to accelerate discovery and experimental investigation of novel metabolic and regulatory pathways of plant peroxisomes.